1992
DOI: 10.1159/000470383
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Seismocardiography for Detection of Coronary Artery Disease

Abstract: Seismocardiography is a noninvasive test being studied for use in conjunction with standard exercise testing to detect changes in cardiac function as a result of exercise-induced ischemia. To test the ability of exercise seismocardiography to detect coronary artery disease, exercise seismocardiograms were recorded on 1,221 patients undergoing routine exercise testing. From these, 204 patients were analyzed who had either coronary angiography or an estimated <2% risk of coronary disease. Sensitivity for detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…9 Taking into account the cut points on the score (S), we can trace the predictive value receiver operating characteristics curve (pv-ROC) plotting the positive predictive value against: 100 − negative predictive value. Moreover, we created a severity score (S) based on the number of arteries n i with percent occlusion indicated by i (i = 1, 2, 3, 4 for levels of occlusion so that S = i n i 4 (i−1) ).…”
Section: Exercise Seismocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…9 Taking into account the cut points on the score (S), we can trace the predictive value receiver operating characteristics curve (pv-ROC) plotting the positive predictive value against: 100 − negative predictive value. Moreover, we created a severity score (S) based on the number of arteries n i with percent occlusion indicated by i (i = 1, 2, 3, 4 for levels of occlusion so that S = i n i 4 (i−1) ).…”
Section: Exercise Seismocardiographymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] SCG is used in conjunction with exercise stress test (ETT) and is useful for the detection of exerciseinduced changes in cardiac muscle contractility that may occur during myocardial ischemia. He realized that the sophisticated technology developed in the 1980s during earthquakes study-seismology-could be applied to cardiology.…”
mentioning
confidence: 99%
“…Substituting this result into (8) we get s(t) = C(Re(J, (f3)Jfl2lt ) cos a -Im(J ($)eP2t ) sina) (10) = C(J ($)COS(27flfmt)COSa -,iJn (/3) S1fl(27flfmt) sina) (11) Finally, using the trigonometric angle-sum relationship we obtain s(t) = C J (f3)COS(2itflfmt + a) (12) which is the desired result. Substituting this result into (8) we get s(t) = C(Re(J, (f3)Jfl2lt ) cos a -Im(J ($)eP2t ) sina) (10) = C(J ($)COS(27flfmt)COSa -,iJn (/3) S1fl(27flfmt) sina) (11) Finally, using the trigonometric angle-sum relationship we obtain s(t) = C J (f3)COS(2itflfmt + a) (12) which is the desired result.…”
Section: Heart Information In the Radar Outputmentioning
confidence: 99%
“…The SCG signal was first shown to be useful in enhancing the diagnostic capability of exercise stress testing for coronary artery disease (CAD) in 1992 [16], and then subsequently demonstrated as capable of evaluating exercise capacity for sports medicine [17]. Furthermore, the results of a large multicenter study demonstrated that combining SCG and ECG signals improved the predictive accuracy of detecting CAD compared to using ECG alone [18].…”
Section: Introductionmentioning
confidence: 99%